1991
DOI: 10.1152/ajprenal.1991.260.4.f579
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of endothelin 1 receptor and signal transduction mechanisms in rat medullary interstitial cells

Abstract: Previous autoradiographic studies have delineated the renal medullas the predominant site of renal endothelin (ET) receptors. Accordingly, cultured rat renal medullary interstitial cells (RMICs) were studied as a target tissue for ET action. Scatchard analysis revealed presence of a single class of high-affinity receptor sites (Kd, 57 +/- 10 pM; receptor density, 749 +/- 124 fmol/mg protein). Relative potency order for displacing 125I-ET-1 was ET-1 greater than ET-2 greater than sarafotoxin greater than big en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
0

Year Published

1992
1992
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 0 publications
2
47
0
Order By: Relevance
“…H7, a protein kinase C inhibitor, had no effect on unstimulated RMIC surface area, but completely blocked the contractile response to ET-1. Hence, ET-1 stimulated RMIC contraction is dependent in part on voltage-insensitive extracellular calcium entry -and is mediated through activation of protein kinase C. ET-1 stimulates RMIC production of PGE2 (13,22), an eicosanoid which can inhibit the vasoconstrictive effect of ET-1 (23). To determine if cyclooxygenase products modify the contractile response to ET-1 in RMIC, cells were treated with indomethacin followed by addition of ET-1 (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…H7, a protein kinase C inhibitor, had no effect on unstimulated RMIC surface area, but completely blocked the contractile response to ET-1. Hence, ET-1 stimulated RMIC contraction is dependent in part on voltage-insensitive extracellular calcium entry -and is mediated through activation of protein kinase C. ET-1 stimulates RMIC production of PGE2 (13,22), an eicosanoid which can inhibit the vasoconstrictive effect of ET-1 (23). To determine if cyclooxygenase products modify the contractile response to ET-1 in RMIC, cells were treated with indomethacin followed by addition of ET-1 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…ET-1 is a 21-amino acid peptide that is the most potent vasoconstrictor known (17). It binds to high affinity receptors on RMIC and elicits an increase in cytosolic-free Ca2+ concentration that is dependent in part upon increases in inositol trisphosphate levels and receptor-operated Ca2+ channels (13). We report that ET-1 causes a long-lasting and potent contraction of cultured rat RMIC.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…First of all, there is scarce information on the two ET receptor subtypes' role in the kidney, and the available evidence is conflicting. On the one hand, results from radioligand binding ( 17), as well as mRNA measurements ( 18), suggest that ETA receptors are located primarily on vascular smooth muscle cells and ETB receptors are found on the tubular epithelial cells. In contrast, there is emerging evidence from whole animal studies with selective agonists and antagonists of ETA and ETB receptors, indicating that at least in the rat, renal vasoconstriction is not mediated by the ETA receptor ( 19,20).…”
Section: Discussionmentioning
confidence: 99%
“…The highest concentrations of immunoreactive ET-1 in the body have been detected in the renal medulla (23). In addition, gene expression and immunoreactive peptides of ET-1 and its receptors have been demonstrated in the renal tissue, especially in the medullary region (23,26,40,42,45). Interestingly, in vivo studies revealed that administration of ET-1 resulted in reduced renal hemodynamics and kidney dysfunction, similar to those found during pneumoperitoneum (9).…”
mentioning
confidence: 90%